USES OF DYES IN DIAGNOSTIC RADIOLOGY: A REVIEW - Yasser Gurmallah Saed Alzahrani, Mohammad Abdullah Ahmed Alessa, Ghadeer Saad Sattem Alenazi, Saeed Saeed Moften Albeladi, Aiyed Raddah Saeed Alkhathami, Ali Mohammed Thabit Alawi, Wajdi Yahya Yahya Alharazi, Ahmed Khazim Ahmed Alqarni, Wejdan Saad Sattam Alenazi, Banan Majid Hamzah Aljehani (Chelonian Research Foundation, 2024)
Dyes have long been a critical component in diagnostic radiology, aiding in the visualization of anatomical structures, differentiation of tissues, and assessment of physiological function. Various classes of dyes, including contrast agents, fluorescent dyes, and radiolabeled substances, are employed in radiological imaging techniques such as X-ray, computed tomography (CT), magnetic resonance imaging (MRI), ultrasound, and nuclear medicine. This review explores the application, mechanisms, and clinical significance of dyes in diagnostic radiology, with a focus on contrast agents, their interactions with imaging modalities, and their role in enhancing diagnostic accuracy. The paper also discusses advancements in dye technology, challenges in their use, and the future directions of diagnostic imaging.